Answers

2014-06-13T08:43:47+08:00
4x + 3y = 3    equation 1
6x + 5y = 1    equation 2

first we need to eleminate 1 varaible by equating eq. 1 to eq.2
4x + 3y - 3 = 6x + 5y - 1
since there is nothing that can be eliminated 
we will multiply each side so that 1 variable will be eleminated.

3(4x + 3y - 3 = 6x + 5y - 1)2

we multiply eqaution 1 by 3 and
we multiply eqaution 2 by 2
we got 

12x + 9y - 9 = 12x + 10y - 2

now 12x will be eliminated:
by transposition
12x + 9y - 9 - 12x - 10y + 2 = 0
-y-7=0
y = -7

substitute the value of y to equation 1 
4x + 3y = 3   
4x + 3(-7) = 3
4x - 21 = 3 
4x = 21 + 3
4x/4 = 24/4
x = 6

checking:
4x + 3y = 3   
4(6) + 3(-7) = 3   
24 - 21 = 3
3 = 3 check
0